Presence of poetry in the singer-songwriter: the Dylan effect - Viñas Piquer, David (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The idea that singer-songwriters can be considered poets has been defended by many people and found its culmination when the Swedish Academy awarded the Nobel Prize in Literature to Bob Dylan in 2016. This paper reviews this idea considering the different stages of evolution of lyric poetry and contrasting them with the creative activity carried out by singer-songwriters. The objective pursued is to show what convergences and divergences really exist between the figure of a singer-songwriter and that of a poet.